Four past midnight - King, Stephen (Hodder & Stoughton, 2011)
At midnight comes the point of balance. Of danger. The instant of utter stillness when between two beats of the heart, an alternative reality can slip through, like a blade between the ribs, and switch you into a new and terrifying world. FOUR PAST MIDNIGHT: four heart-stopping accounts of that moment when the familiar world fractures beyond sense, the fragments spinning away from the desperate, clutching reach of sanity ...